Our Lady of Benoni - Mda, Zakes (Wits University Press, 2012)
Zakes Mda's satire is a kaleidoscopic display of the extremes to which men (and by implication women) are prepared to go in terms of valuing what is 'virginal'. Mda presents us with the consequences of transgression: that which is seen as polluted and judged to be dangerous to the good health and purity of a group, a society, a culture. Taboos, superstition, customs and moral ethics become the subjects of inquiry and are, at times, subjected to ribald satire. This play cuts into a virtuoso style of theatre that can in no way be confused with the objectives and methods of conventional realism. Mda establishes a unique style and tone that is innovative, entertaining and challenging. It fuses satirical elements derived from classical poetry with a modernist sensibility that synthesises Brechtian and Absurdist features of theatricality, using characters as types and montage. Above all, in this work there is a profound exploration of what it means to operate in the politically charged landscape that defines post-apartheid South Africa with its cultural pluralities and differentials in access to resources and agency. Stylistically adventurous and unafraid to deviate from conventionally accepted norms, Mda is iconoclastic in his handling of the ways in which attitudes to power, superstition, ethics and sex are constructed. The cultural discourse of patriarchy and the 'regime of truths' regarding ideals and taboos defining female sexuality, its obligations, and its custodianship are the focus of this play.